Longitudinal distribution of the field intensity of a circular focused aperture - Dolzhikov , V.V. (Radiotekhnika, 2021)
Microwave and millimeter-wave antennas focused in their Fresnel zone, which are usually named as near-field focused (NFF) antennas, are becoming increasingly popular. Indeed, when compared to conventional far-field focused antennas, they can guarantee performance improvement at a relatively limited implementation cost, in short-range communication systems, wireless power transfer arrangements, remote nondestructive sensing setups, and radiofrequency identification apparatus, among many others. In this paper, analytical expressions are obtained for calculating the main parameters characterizing the longitudinal distribution of the circular focused aperture field intensity with a relatively large diameter (2R/λ≥10) : the displacement of the intensity maximum relative to the focal point, focusing gain and depth of focus. Cases of uniform and decreasing amplitude distributions of the excitation field are considered. The found approximate relations make it possible to determine the values of the above parameters for any values of the longitudinal coordinate of the focal point, lying both in the Fresnel zone and in the far zone. Comparison with numerical calculations showed that the error in the obtained parameter values does not exceed 5%. The results of this paper will be useful when calculating the field of antennas in the form of a circular focused aperture, as well as focused antenna arrays operating in the Fresnel zone.